Evaluation conditions to treat slime water with coagulant-bioflocculant by orthogonal design - Kang, Yu; Peng, Cheng; Zhang, Fengyuan; Xing, Jie; Li, Lixin; Ma, Fang; Liu, Yan (Tecnología y ciencias del agua, 2022)
In this study, a new type of microbial flocculant combined with Poly-aluminum ferric chloride (PAFC) coagulant was utilized in the coagulation-flocculation experiment of slime water. The removal effects of PAFC dosage, the bioflocculant dosage, and pH on the turbidity and Chemical Oxygen Demand (COD) of the coal slime water were investigated. The results illustrated that the best conditions for removing slime water turbidity and COD by single factor test were as follows: the dosage of PAFC was 37.5 mg/l, the dosage of bioflocculant was 0.75 mg/l, and the pH was 7.0. The most influential factors for turbidity and COD removal were identified through orthogonal test methodology as pH and PAFC dosage, respectively. The coagulation-flocculation of the best condition was a dosage of PAFC of 50.0 mg/l, the dosage of bioflocculant was 0.5 mg/l, and the pH was 7.0. Under this condition, the turbidity removal efficiency of 93.2Â % and the COD removal efficiency of 47.2Â % were obtained.